Vintage Materialities in Music - Forment, Bruno 1978-; Vintage Materialities in Music Orpheus Instituut, Ghent 28-30 June 2023; Vaes, Luk; Parra Cancino, Juan; Koninklijk Conservatorium Brussel (Belgium); LUCA School of Arts (Leuven and Ghent, Belgium) (Ghent Orpheus Instituut; KCB; LUCA School of Arts, 2023)
Once a term from winemaking and a synonym of high quality, now a standard epithet of any object that is sought after on account of its rarity, unicity, or antiquity, ‘vintage’ has sparked (sub)cultures, industries, and communities. In music, vintage refers mostly to instruments or apparatuses that, after a period of obsolescence, are being rediscovered, revalued, reproduced, or revamped—electric guitars, effects pedals, analogue synthesisers, drum machines, amplifiers, recording equipment, sound carriers, etc. The scope, appeal, and user groups of vintage gear are becoming wider by the day. Aesthetically speaking, vintage materialities are defining the sound and look of multiple styles of music, just as harpsichords, gut-stringed violins, and valveless trumpets are characterising ‘early music.’ However, vintage materialities in music transcend issues of historically informed performance, and they confront artists and scholars with unanswered questions: On what grounds can obsolete technologies for music production and performance become desirable again in an era of high-tech, across different genres, and in both the professional and amateur spheres? In what ways do vintage materialities and their technical affordances mediate or challenge present-day creative and performative practices? How do vintage materialities respond to cultures, discourses, politics, and economies of, among others, retro style, nostalgia, afro- and retrofuturism, and lo-fi?
FRIS
1
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; HIPEX: Historical Performance Practices of Experimental Music; Music, Thought and Technology; Organology; Antiquarianism